تغیير الأحكام بتغیير العرف و المصلحۃ و الزمان: Effects of custom, expediency (Public Interest) and change of time on jurisprudential Rules - Khan, Shahbaz (Al-Amīr Research Journal for Islamic Studies, 2023)
The concept of "تغيير الأحكام بتغيير العرف والمصلحة والزمان" refers to the principle in Islamic jurisprudence that laws and rulings can be modified or adapted based on changing customs, public interest, and the context of time. This principle acknowledges the flexibility within Islamic law to address evolving societal needs while remaining rooted in the core principles of justice and equity. All of them have been described in the Qur’an and Sunnah with such importance, that by changing them, there is room in the rulings. How much and to what extent that scope is created will be reviewed in the following article and the opinions of the jurists will be presented in this regard. Keywords: Islamic jurisprudence، customs, public interest, context of time.